2018
DOI: 10.18203/2394-6040.ijcmph20184727
|View full text |Cite
|
Sign up to set email alerts
|

Profile of HIV sero-positive attendees: an integrated counselling and testing centre record based retrospective study

Abstract: Background: The sustainable development goal target is to end the AIDS epidemic by 2030. HIV continues to be a major global public health issue, having claimed more than 35 million lives so far. The objectives of the study were to find out the pattern of socio-demographic profile among HIV sero-positive patients attending ICTC centre in SVIMS, Tirupati and to study the risk behaviour pattern among HIV sero-positives.Methods: Retrospective cross sectional study was undertaken at ICTC Centre, SVIMS, SPMC (W), Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The most common mode of HIV transmission observed in our study was through unprotected heterosexual contact (97.4%). This finding is consistent with other studies that identified heterosexual sex practice as the predominant mode of HIV transmission (96.1%-97.76%) [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…The most common mode of HIV transmission observed in our study was through unprotected heterosexual contact (97.4%). This finding is consistent with other studies that identified heterosexual sex practice as the predominant mode of HIV transmission (96.1%-97.76%) [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…8,9 However these results were in contrast to a study done in Tirupati where the number of clients decreased over years and no much difference was observed in prevalence. 10 Heterosexual mode of transmission was responsible for sero-positivity among of HIV positive clients as noted with other studies. The married to unmarried ratio was 7.12:1 as against 4.47:1 (228/51) in Meerut study.…”
Section: Discussionsupporting
confidence: 53%